Discovery and Characterization of CD12681, a Potent RORγ Inverse Agonist, Preclinical Candidate for the Topical Treatment of Psoriasis. (6th February 2018) - Ouvry, Gilles; Atrux‐Tallau, Nicolas; Bihl, Franck; Bondu, Aline; Bouix‐Peter, Claire; Carlavan, Isabelle; Christin, Olivier; Cuadrado, Marie‐Josée; Defoin‐Platel, Claire; Deret, Sophie; Duvert, Denis; Feret, Christophe; et al.
Abstract: With possible implications in multiple autoimmune diseases, the retinoic acid receptor‐related orphan receptor RORγ has become a sought‐after target in the pharmaceutical industry. Herein are described the efforts to identify a potent RORγ inverse agonist compatible with topical application for the treatment of skin diseases. These efforts culminated in the discovery of N ‐(2, 4‐dimethylphenyl)‐ N ‐isobutyl‐2‐oxo‐1‐[(tetrahydro‐2 H ‐pyran‐4‐yl)methyl]‐2, 3‐dihydro‐1 H ‐benzo[ d ]imidazole‐5‐sulfonamide (CD12681), a potent inverse agonist with in vivo activity in an IL‐23‐induced mouse skin inflammation model. Abstract : You′re gonna hear me ROR ! The pressure is on to find RORγ modulators, which show promise in the treatment of autoimmune diseases, specifically psoriasis. The optimization of heterobicyclic sulfonamides is presented here with a focus on minimizing lipophilicity. These efforts culminated in the identification of CD12681, a potent RORγ inverse agonist compatible with topical application and efficacy in vivo.